Agenda-setting and analysis of contributions of Nigerian newspapers to poverty-reduction - Akinsulire, Tolulope; Olatunji, Rotimi Williams (Asian Journal Collaboration of Social Environmental and Education, 2025)
Background: Poverty remains one of the most pressing socio-economic challenges in Nigeria, with a large proportion of the population living below the national poverty line. The press plays a vital role in shaping public discourse, setting agenda for the society, and analysing topical issues impacting the society. Although previous studies have explored media representation of poverty, there remains a gap in regionally comparative analyses of how Nigerian newspapers cover poverty-related issues. This study aimed to examine the types of poverty-related issues frequently covered in Nigerian newspapers, determine regional differences in coverage patterns, and assess the prominence accorded to such issues. Methods: The study employed quantitative content analysis as its method, using a composite sampling technique to select 322 newspaper editions from Vanguard (South-based) and Daily Trust (North-based) over a three-year period. Data were coded using a structured content coding guide. Findings: The findings revealed a total of 737 poverty-related stories, with Daily Trust publishing slightly more (376) than Vanguard (361). Regional framing differences were evident: Daily Trust focused more on education (23.4%), healthcare (19.7%), and sanitation (10.4%), while Vanguard emphasized food insecurity (19.4%), unemployment (14.4%), and inadequate social welfare (10.2%). However, most of the stories were placed on inside pages, indicating low prominence. The analysis suggests that although both newspapers contribute to agenda-setting on poverty, the limited front-page coverage may hinder the visibility required to drive meaningful policy engagement. Conclusion: The study concludes that Nigerian press needs to partner more with relevant stakeholders, towards the realisation of the aspirations of the United Nations’ Sustainable Development Goal (SDG) on Poverty alleviation. Novelty/Originality of this article: This research provides new insights as it offers a regional comparative perspective to poverty discourse in Nigerian media studies.